Root Herbivores Drive Changes to Plant Primary Chemistry, but Root Loss Is Mitigated under Elevated Atmospheric CO2 - McKenzie, Scott W.; Johnson, Scott N.; Jones, T. Hefin; Ostle, Nick J.; Hails, Rosemary S.; Vanbergen, Adam J. (Frontiers in Plant Science, 2016)
Above- and belowground herbivory represents a major challenge to crop productivity and sustainable agriculture worldwide. How this threat from multiple herbivore pests will change under anthropogenic climate change, via altered trophic interactions and plant response traits, is key to understanding future crop resistance to herbivory. In this study, we hypothesised that atmospheric carbon enrichment would increase the amount (biomass) and quality (C:N ratio) of crop plant resources for above- and belowground herbivore species. In a controlled environment facility, we conducted a microcosm experiment using the large raspberry aphid (Amphorophora idaei), the root feeding larvae of the vine weevil (Otiorhynchus sulcatus), and the raspberry (Rubus idaeus) host-plant. There were four herbivore treatments (control, aphid only, weevil only and a combination of both herbivores) and an ambient (aCO2) or elevated (eCO2) CO2 treatment (390 versus 650 ± 50 μmol/mol) assigned to two raspberry cultivars (cv Glen Ample or Glen Clova) varying in resistance to aphid herbivory. Contrary to our predictions, eCO2 did not increase crop biomass or the C:N ratio of the plant tissues, nor affect herbivore abundance either directly or via the host-plant. Root herbivory reduced belowground crop biomass under aCO2 but not eCO2, suggesting that crops could tolerate attack in a CO2 enriched environment. Root herbivory also increased the C:N ratio in leaf tissue at eCO2, potentially due to decreased N uptake indicated by lower N concentrations found in the roots. Root herbivory greatly increased root C concentrations under both CO2 treatments. Our findings confirm that responses of crop biomass and biochemistry to climate change need examining within the context of herbivory, as biotic interactions appear as important as direct effects of eCO2 on crop productivity.